Problematic Mobile Phone Use and Mental Health Problems in Adolescents with Mild Intellectual Disability - Arsić, Bojana B.; Gajić, Anja M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
In the last few decades, more people have been using mobile phones, even people with intellectual disabilities (ID). The most common consequence of excessive use of mobile phones is the emergence of mental health (MH) problems. This research aims to determine the predictors and correlation between problematic mobile phone use and MH problems in adolescents with mild ID. The sample comprised 54 adolescents of both genders who have mild ID and who attend the Vocational High School in Belgrade. The Problematic Cellular Phone Use Questionnaire was used to measure the characteristics of the respondents’ use of mobile phones and the Depression, Anxiety and Stress Scale was used to measure MH problems. It was found that adolescents with mild ID have a statistically significantly high degree of problematic mobile phone use. Younger adolescents, those who use a mobile phone more time during the day and adolescents who use psychoactive substances have a higher degree of problematic mobile phone use. Girls have more MH problems compared to male adolescents. In addition, adolescents with mild ID who have a higher degree of problematic mobile phone use have more MH problems, and the presence of MH problems in one domain is positively correlated with the presence of others. In conclusion, we highlight the limitations as well as recommendations for future researchers and practitioners working with this population.